Hak Nafkah dan Dinamika Ekonomi Digital: Dampak Gig Economy Terhadap Peran Suami Istri dalam Keluarga Muslim - Ahmad Sun’an Pambudi; Masruhan; Nurlailatul Musyafaah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapidly growing gig economy phenomenon in the digital era has brought significant changes to the economic structure of Muslim families, particularly regarding the obligation to provide for a living, which according to Islamic jurisprudence is the husband's responsibility. The gig economy, based on flexible work, short-term contracts, and unstable income, creates new dynamics in husband-wife relations, the division of gender roles, and the concept of qiwāmah (compensation) within the household. This study aims to examine how the gig economy affects the implementation of the obligation to provide for a living and how Muslim families renegotiate the economic roles between husband and wife during the digital transformation. The study used a qualitative approach, analyzing classical and contemporary literature, socioeconomic data on gig workers, and interpreting the context using the maqāṣid al-shari'ah framework. The results show that the obligation to provide for a living remains normatively with the husband, but the reality of digital income instability encourages the emergence of collaborative patterns in meeting household needs. The gig economy also causes psychological stress for husbands who feel they have lost stability and their traditional position as primary breadwinners, while simultaneously enhancing women's economic roles through digital employment opportunities. These findings demonstrate the need to reinterpret the concepts of qiwāmah and sustenance in the context of the modern economy, and demand public policies that protect gig workers to ensure the continued well-being of Muslim families.